Enabling High Loading in Single‐Atom Catalysts on Bare Substrate with Chemical Scissors by Saturating the Anchoring Sites. Issue 19 (8th March 2022) - Li, Ang; Kan, Erjun; Chen, Shuangming; Du, Zhengwei; Liu, Xuan; Wang, Tongyu; Zhu, Wenjin; Huo, Hailing; Ma, Jingjing; Liu, Dong; Song, Li; Feng, Hao; et al.
Abstract: Atomically dispersed metal catalysts often exhibit high catalytic performances, but the metal loading density must be kept low to avoid the formation of metal nanoparticles, making it difficult to improve the overall activity. Diverse strategies based on creating more anchoring sites (ASs) have been adopted to elevate the loading density. One problem of such traditional methods is that the single atoms always gather together before the saturation of all ASs. Here, a chemical scissors strategy is developed by selectively removing unwanted metallic materials after excessive loading. Different from traditional ways, the chemical scissors strategy places more emphasis on the accurate matching between the strength of etching agent and the bond energies of metal‐metal/metal‐substrate, thus enabling a higher loading up to 2.02 wt% even on bare substrate without any pre‐treatment (the bare substrate without any pre‐treatment generally only has a few ASs for single atom loading). It can be inferred that by combining with other traditional methods which can create more ASs, the loading could be further increased by saturating ASs. When used for CH3 OH generation via photocatalytic CO2 reduction, the as‐made single‐atom catalyst exhibits impressive catalytic activity of 597.8 ± 144.6 µmol h −1 g −1 and selectivity of 81.3 ± 3.8%. Abstract : The low loading of single‐atom catalysts makes it difficult to improve the overall activity. Here, a chemical scissors strategy is reported to saturate the anchoring sites for single atoms, which elevates the loading of Pd single atoms to 2.02 wt% even on bare substrate with only a few anchoring sites. The catalysts exhibit an improved photocatalytic CO2 reduction activity.